Sexual Risk Behavior in HIV‑Uninfected Pregnant Women in Western Uganda - Theuring, Stefanie; Kenyonyozi, Rubagumya; Rubaihayo, John; Wanyenze, Rhoda (Archives of Sexual Behavior, 2021)
Our aim was to identify sexual risk behavior among HIV-negative pregnant women in Kabarole District, Uganda, by conducting a cross-sectional study among 1610 women within three healthcare settings. One in six women engaged in HIV-specific risk behaviors including multiple sexual partners or alcohol abuse; 80% of the pregnant women reported to generally abstain from using condoms. In multivariate analysis, predictors of sexual risk behavior included being a client of the public health facilities as compared to the private facility (AOR 3.6 and 4.8, p < 0.001), being single, widowed or divorced or not cohabiting with the partner (AOR 4.7 and 2.3, p < 0.001), as well as higher household wealth (AOR 1.8, p < 0.001) and lack of partner status knowledge (AOR 1.6, p = 0.008). Self-estimated risk perception was linked with engagement in HIV-related risk behaviors except for alcohol abuse. Our findings indicate that reducing risky behaviors in pregnancy in order to prevent HIV should be a high-priority public health concern.